Energy, exergy and heat transfer performance investigation of a vapor compression air conditioning system / Jamal Uddin Ahamed - Jamal , Uddin Ahamedf (2012)
In this thesis, the energy, exergy and heat transfer performance of a split type air-conditioning unit are evaluated and the benefits of changing refrigerant (R22) with an alternative mixture (M1) are investigated. In this regard, a test rig consisting of a split air-conditioner was designed to work with R22. The test was conducted for two refrigerants; the first one was R22, the second one was a mixture of R22 and R290 with a mass ratio of 3:1. The inlet and outlet temperature and pressure fluctuations at the compressor, evaporator, condenser and expansion device were measured by a digital data logger. The compressor power consumption was also carefully monitored by a digital power meter. The results obtained from the two different refrigerants were compared. It was found that the coefficient of performance of the mixture was about 10-15% higher than that of R22 for the ambient temperature, Ta= 27°C. The result reveals that the coefficient of performances of the refrigerants increased with the increase of evaporator temperature and decreased with the increase of condenser temperature. The seasonal energy-efficiency ratio was found to be higher at lower ambient temperature. It was found that the compressor energy usage was increased up to 10-17% with the increase of condenser temperature. The test results show that by using M1, energy consumption can be saved up to 5.22% in the vapor compression air-conditioning system. Exergy efficiency analysis was conducted for all the components of the vapor compression system at different evaporator temperature. This analysis also deals with the effect of evaporator, condenser and ambient temperatures on exergy losses. The result shows that exergy losses decreased with the increase of evaporator temperature and ambient temperature. However, the exergy losses increased with the increase of condenser temperature. It was found that about 60- 65% of the exergy losses were taken place at the condenser. Exergy efficiency of the system for the mixture was found to be higher than that of R22. The refrigerating effect of the airconditioner was increased up to 2 to 6% while using the mixture (M1) instead of R22 at different evaporator temperatures. The heat transfer coefficient of M1 was measured higher than that of R22 at all working conditions and it was increased with the increase of mean evaporating temperature. At the working conditions, cooling capacity of M1 was higher than that of R22. It was found that the heat rejection ratio varied with different operating temperatures. It was also found that by increasing the set point by 4°C (from 20°C to 24 °C); the energy consumption can be saved up to 24.40%. Finally, a correlation for the coefficient of performance of the system based on different condenser temperatures, ambient temperatures and evaporator temperatures have been developed. Based on the results of this work, it can be concluded that the mixture (M1) is the suitable alternative for the replacement of R22 based on energy, exergy and heat transfer performance.